Why does New Zealand have such poor outcomes from colorectal cancer?: the importance of the pre-diagnostic period - Ross Lawrenson; Jon Emery; David Weller; Mark Elwood; Tim Stokes; Rawiri Keenan; Lynne Chepulis; Tania Blackmore; Melissa Firth (CSIRO Publishing, 2021)
ABSTRACT INTRODUCTIONOver 3000 cases of colorectal cancer (CRC) are diagnosed annually in New Zealand. The proportion of late stage diagnoses is higher than in similar countries, and highest in Māori and Pacific patients. Survival outcomes are poorer than for people in Australia and poor for Māori and Pacific peoples. A regional screening programme is not yet available to the entire target population (60-74 years). AIMThis study reviews research investigating the pre-diagnostic pathway for CRC in New Zealand and how this may contribute to poorer outcomes. METHODSThis was a scoping review of original articles examining the pre-diagnostic period for CRC published on the PubMed database between 2009 and 2019. Findings were interpreted within the Model of Pathways to Treatment framework and in context of international evidence. RESULTSIn total, 83 publications were assessed; eight studies were included. Studies were mainly older than 5 years, qualitative, and focused on screening. Facilitatory factors for the appraisal and help-seeking intervals increased CRC public awareness and the critical role of general practitioners. No specific facilitatory or inhibitory factors were identified for the diagnostic interval, but two studies found that time frames did not meet national and international targets. One study discovered longer pre-diagnostic intervals were associated with younger age at diagnosis. DISCUSSIONLimited recent research has investigated the CRC pre-diagnostic pathways in NZ. Identification of facilitatory and inhibitory factors and implementation of appropriate strategies to improve them alongside the wider uptake of the screening programme may improve stage at diagnosis and outcomes for New Zealand CRC patients.